Rewriting and reception in and of the bible - Høgenhaven, Jesper; Nielsen, Jesper Tang; Omerzu, Heike; Müller, Mogens (Wissenschaftliche Untersuchungen zum Neuen Testament, 2018)
Cover -- Preface -- Table of Contents -- Jesper HÃ¸genhaven, Jesper Tang Nielsen, Heike Omerzu: Introduction: Rewriting and Reception in and of the Bible -- Part I Rewriting and Reception in the Bible -- Ancient Judaism -- Jesper HÃ¸genhaven: Fortschreibung und Kanonisierung in der Bibliothek von Qumran: Bemerkungen mit besonderem Hinblick auf Genesis-Kommentar A (4Q252) -- 1 Was sind âºautoritative Texteâ¹ im Hinblick auf die Qumran-Rollen? -- 2 Vorstufen zur Kanon-Bildung? Fortschreibung und Kommentar -- 3 Spiegeln Fortschreibung und Kanonisierungverschiedene Grundhaltungen wider? -- 4 Der Genesis-Kommentar von Qumran (4Q252) -- 5 Auslegung durch Fortschreibung(Â»RewritingÂ«) im Genesis-Kommentar? -- 6 Auslegung durch Kommentierung imGenesis-Kommentar? Zwei Beispiele -- 7 Gattung und Auslegungsstrategie im Genesis-Kommentar 4Q252 -- 8 Folgerungen und Schlussbemerkungen -- Ingrid Hjelm: The Coming of a âºProphet Like Youâ¹ in Ancient Literature -- 1 The Masoretic Bible -- 2 The Samaritan Pentateuch -- 3 The Coming of a Prophet in Samaritan Tradition -- 4 A prophet Like Moses in the Masoretic Tradition -- 5 The Coming of a Prophet in the New Testament -- Thomas L. Thompson: âºRewritten Bibleâ¹ or Reiterative Rhetoric: Examples from Yahwehâs Garden -- 1 Rewritten Bible and the Rhetoric of Imitation -- 2 Yahwehâs Well-watered Garden -- 3 Paradise Lost -- 4 Noahâs vineyard: a brief reiteration -- 5 Â»As well-watered as Yahwehâs garden, like the land of EgyptÂ« (Gen 13:10) -- 6 Returning to the Tree of Life -- 7 The Song of the Vineyard -- 8 The Poor Manâs Garden -- Siegfried Kreuzer: New Testament Quotations and the Textual History of the Septuagint -- 1 Introduction -- 2 New observations -- 3 New Testament quotations as witnessesto the text of the Septuagint -- 4 Conclusions -- New Testament